From doorstep to Internet: consumer protection againts unfair trade practices in Malaysia - Amin, Naemah (2010)
Doorstep selling or also known as a door-to-door sale is a common method of business of direct selling companies. Unlike sale in a retail outlet, doorstep selling has raised particular consumer protection issues. These include interference with privacy, coercion, restriction on consumer choice, lack of information about the product and the supplier and other unethical marketing and selling practices. For these reasons, doorstep selling has been the subject of scrutiny by the legislators in most countries where direct selling business is very popular. In Malaysia, it is governed by the Direct Sales Act 1993. After the Act has been enforced for nearly 15 years, its adequacy in controlling the direct selling industry and protecting the consumers is still questionable. Many of direct selling companies have now ventured into new method of business by utilizing internet. This latest development exposes the consumer to certain problems not raised in door-to-door sale which still involve face to face communication. Thus it is the main aim of this paper to examine the relevant laws in Malaysia that provide certain protection to consumers against trade malpractices in direct selling transactions particularly e-direct selling. The main focus of discussion is the Direct Sales Act 1993 including the 2010 Amendment to the Act.